Reporte de lesiones en murciélagos causadas por el uso incorrecto de collares plaÌsticos como método de marcaje - Rodríguez-Posada, Miguel E.; Santa-SepuÌlveda, María Alejandra (THERYA, 2013)
We record the injuries caused to two bats marked with a self-locking plastic cable tie as a necklace which produced a deep abrasion in the skin of neck area. This is the first report about negative effects caused by the inadequate use of marking methods in bats from Colombia. Key words: bat handling, injuries, Chiroptera, marking necklaces, self-locking plastic cable-ties.